IN-SITU PERFORMANCE OF SU-FREI BRIDGE BEARINGS - van Galen, Zachary (My University, 2023)
Stable Unbonded Fibre Reinforced Elastomeric Isolators (SU-FREI) have been investigated extensively for seismic applications, with over 20 years of literature supporting their use in isolation of structures as an alternative to conventional Steel Reinforced Elastomeric Isolators (SREI). Preliminary investigations have been conducted into their potential use as bridge bearings, where they could provide an alternative to unreinforced and steel reinforced elastomeric bearings. SU-FREI offer a number of potential advantages in this application relative to SREI, including compactness due to thinner reinforcement layers, ease of installation, rotational tolerances, and ease of manufacture. Recently, SU-FREI have been installed under certain highway bridges along the 407 ETR where the previous unreinforced elastomeric bearings had experienced failure. Monitoring has been conducted by Associated Engineering for the 407 ETR Corporation. Data was collected from this monitoring program and field visits have been conducted to observe the condition of the bearings. The original design process used for the SU-FREI bearings has also been reviewed. The monitoring data was compared against design calculations, and the behavior of the SU-FREI analysed to determine whether they meet performance expectations and are suitable for further use as bridge bearings. It was found that some SU-FREI had experienced degradation, including the appearance of an unidentified liquid. The causes of deterioration were investigated and postulated to be primarily related to design limitations imposed by the geometry of the bridges, original design calculation assumptions, and installation issues. Where these factors were not present, the SU-FREI bearings were found to have experienced little to no deterioration. Furthermore, it was determined through comparative design calculations that the FREI outperformed equivalent SREI with regard to rotational capacity. Recommendations have been developed for future deployment of SU-FREI as bridge bearings. Based on the results of initial deployments, larger-scale employment of SU-FREI in this application should be considered.
Keywords: Elastomer; Isolator; Bearing; Rubber; FREI; Carbon Fibre; SU-FREI; Fibre Reinforced; Unbonded; Bridge; Monitoring; Bridge Bearing